Trend analysis of disease burden in China from 1990 to 2019 - Xiao-Yu YANG; Dong-Yu CHEN; Hong-Xin WANG; Wen-Long FAN; Yu-Qing HE (Yixue xinzhi zazhi)
Objective To understand the current situation of disease burden in China and its changing trend from 1990 to 2019.Methods Using the Global Burden of Disease Study (GBD 2019) data, this study analyzes the changes in the order of diseases causing the loss of disability adjusted life years (DALY) among Chinese people of different ages and genders and the rate of change from 1990 to 2019, and explores the changes in the main risk factors affecting the health of Chinese residents.Results In 2019, the DALY loss for all diseases in China reached 380 million per-son-years, and the total DALY rate decreased from 34,832.88/100,000 in 1990 to 26,871.41/100,000 in 2019, a de-crease of 22.86%. Over the past 30 years, stroke, ischemic heart disease, chronic obstructive pulmonary disease and tracheal, bronchus and lung cancer have always been the top causes of DALY loss in China. Among them, chronic non-communicable diseases are the main causes of DALY loss in women, while cancer and road injuries are the main causes in men. Because the influencing factors for different age groups are not the same, the DALY loss among people aged 0-9, 10-24, 25-49, 50-74 and over 75 was also not the same, and this changed by -87.07%, -57.11%, 2.13%, 53.33% and 129.72% respectively compared with 1990. Tobacco, high systolic blood pressure, dietary risk factors and air pollution are the most important risk factors affecting population health in China. The impact of high body-mass index on population health is still increasing.Conclusion From 1990 to 2019, the overall health status of Chinese residents improved, and non-communicable diseases accounted for the largest proportion of the disease burden, which gradually increased among the elderly population. It is necessary to take the corresponding effective preventive measures for different age groups and risk groups, and strengthen the monitoring of high-risk groups, so as to further reduce the disease burden.